2017
DOI: 10.3347/kjp.2017.55.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Subsets of Inflammatory Cytokine Gene Polymorphisms are Associated with Risk of Carcinogenic Liver Fluke Opisthorchis viverrini-Associated Advanced Periductal Fibrosis and Cholangiocarcinoma

Abstract: Opisthorchis viverrini infection induces chronic inflammation, and a minor proportion of infected individuals develop advanced periductal fibrosis (APF) and cholangiocarcinoma (CCA). Inflammatory cytokines and/or their gene polymorphisms may link to these biliary pathologies. We therefore investigated associations among cytokine gene polymorphisms and cytokine production in 510 Thai cases infected with O. viverrini who presented with APF+ or APF−, as established by abdominal ultrasonography as well as in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…In addition, the association between Anisakis and tumorigenic potential is also not completely understood. Helminths such as flukes (among several, including Schistosoma haematobium, Opisthorchis viverrini, and Clonorchis sinensis ) are capable of significant tumor-promoting activity [ 17 , 18 , 19 ]. Reports of tumor co-localization with Anisakis L3 and L3 mimicking metastatic lesions are increasing [ 20 , 21 , 22 ] and, interestingly, cases have been reported mainly in countries with a higher prevalence of anisakiasis [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the association between Anisakis and tumorigenic potential is also not completely understood. Helminths such as flukes (among several, including Schistosoma haematobium, Opisthorchis viverrini, and Clonorchis sinensis ) are capable of significant tumor-promoting activity [ 17 , 18 , 19 ]. Reports of tumor co-localization with Anisakis L3 and L3 mimicking metastatic lesions are increasing [ 20 , 21 , 22 ] and, interestingly, cases have been reported mainly in countries with a higher prevalence of anisakiasis [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although frequencies of IFN-γ +874T/A SNP were examined in Thai subjects with different diseases and healthy control, 15,16 our study has reported the genotypes and alleles in PLWH. Previous studies indicated the +874 TT genotype as a high IFN-γ producer 3,4 and the AA genotype appeared to be associated with the susceptibility to HIV infection in Indian and Brazilian ethnic groups.…”
Section: Resultsmentioning
confidence: 91%
“…PFIC2 represents a specific, previously unrecognized risk for HCC in infants. In BSEP deficiency, there is poor excretion of bile salts through the canalicular membrane, resulting in constant exposure of hepatocytes to bile salts, leading to chronic inflammation and carcinogenesis (90,91,108,(134)(135)(136)(137)(138)(139)(140)(141)(142). HCC occurs in 5-15% of pediatric patients with BSEP deficiency, mostly in the second year of life (143)(144)(145)(146).…”
Section: Progressive Familial Intrahepatic Cholestasis Typementioning
confidence: 99%